/ How to Defend Yourself: the Emotional Component of Media Manipulation: / - Davidović, Jovana (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2022)
Post-turth media manipulation techniques dominantly provoke the emotional response in media audience. Fake news, as a specific post-truth subtype, present fabricated information direcrted to a specific media goal, usually motivated by clear economic and political intentions. Media and information literacy, thus, as a logical response to media manipulation, advocate a critical evaluation of the media content. However, in this paper, we argue about infomation literacy as the first and foremost strategy of defense against fabricated information focused on emotional reaction. We use literature framework to outline techniques which serve as protectors against various forms of media manipulation, such as the ability to observe and investigate the credibility of content, awareness of the alternative information, as well as the possibilities for ethical dissemination of information.